Pengaruh Latihan Continuous Running Terhadap Peningkatan Kebugaran Jasmani - Amni, Hazrina; sumaryanti, Sumaryanti; Wulandari, Indri; Widyarto, Setyawan; Agus, Apri; Sukarmin, Yustinus (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
This study aims to determine the effect of Continuous Running Exercise on Increasing Physical Fitness for S1 students of the Sports Science Study Program, Faculty of Sports Science, Padang State University class of 2021/2022. The research method used in this research is a quasi-experimental method. The population in this study were 215 undergraduate students of the FIK UNP Sports Science Study Program, class of 2021/2022. The sampling technique was carried out by purposive sampling, with a total sample of 20 people. The data collection technique uses a physical fitness test research instrument with a 1600 m rockport run. The results of the study were analyzed statistically using a comparison test (t-test) at a significance level of 5%. The results of this study indicate that the average level of physical fitness of the respondents before being given treatment was (45.30), whereas after being given treatment it was (50.35). There is a significant effect of Continuous Running Exercise on Increasing Physical Fitness of Students of the Sports Science Study Program, Faculty of Sports Science, Padang State Universitywith the results showing the tcount value (4.25) > ttable value (1.73).